Developing an optimal supply model ( OSM ) of commercial property in housing scheme - Mohd. Ali, Hishamuddin; Sipan, Ibrahim @ Atan; Nq, Ying Qian (Universiti Teknologi Malaysia, 2004)
In 1997, economic crisis has significantly affected the property market in Malaysia particularly in the commercial property sector. Oversupply in shop houses sub-sector occurred in many states and majority of the unsold unit were confined to Johor. In this context, a planning standard which allots 10% of the total residential unit in a particular housing scheme to be built with shop houses is introduced. However, the oversupply problem is still lingering until now. Therefore, is this planning standards provision in line with the market needs? Hence, the purpose of this study is to examine the performance of shop houses and to develop an optimum supply model of shop houses in Skudai. To achieve these objectives, data is collected from Property Market Report, JPPH transaction records, interview with MPJBT and JPPHs officers as well as inspection in the study area. Descriptive and MRA analysis are adopted in this study. The results show that shop houses market in Skudai has not much change from year 1999-2006 after the 1997s economic crisis. Oversupply problems still exist in certain housing schemes. The developed optimum supply model shows that the optimum supply for shop houses in Skudai housing scheme approximately is 10% of the total residential units which is same as allotted by the planning standard. The main factors influence the shop houses supply are rental and total residential units in the housing scheme. Nevertheless, the independent variables for the model are limited and it is still subjected to other factors such as location. Thus, for further study, it is suggested to include other relevant factors into the model in order to predict the optimum supply of shop houses more accurately. As a conclusion, a property supply should equilibrium to its market needs. The factors influencing the supply should be taken into consideration to reduce the market disequilibriums problems.